Expression and Purification of the Arabidopsis E4 SUMO Ligases PIAL1 and PIAL2 - Konstantin Tomanov; Andreas Bachmair (Bio-Protocol, 2015)
The proteins PIAL1 (At1g08910) and PIAL2 (At5g41580) are members of the recently discovered group of plant E4 SUMO ligases. This protocol allows quick and simple expression of the recombinant proteins in Escherichia coli (E. coli) and subsequent affinity purification using a maltose binding protein (MBP) tag. The proteins can be used in SUMOylation reactions, where the MBP part of the protein can be detected with a commercially available antibody, or additional purification steps can be applied.